Modelling quantities and qualities (Q&Q) of faecal sludge in Hanoi, Vietnam and Kampala, Uganda for improved management solutions - Miriam, Englund; Juan, Pablo Carbajal; Magalie, Bassan; An, Thi Hoai; Viet-Anh, Nguyen; Linda, Strande (Journal of Environmental Management, 2020)
The importance of faecal sludge management is gaining recognition. However, methods are still lacking to reasonably estimate the quantities and qualities (Q&Q) that need to be managed, which makes the planning for and implementing of management solutions quite difficult. The objective of this study was to collect and analyse Q&Q of faecal sludge at a citywide scale, and to evaluate whether “SPA-DET” data (=> spatially analysable - demographic, environmental and technical) could then be used as predictors of Q&Q of faecal sludge. 60 field samples and questionnaires from Hanoi and 180 from Kampala were analysed. Software tools were used in an iterative process to predict total solids (TS) and emptying frequency in both Hanoi, Vietnam and Kampala, Uganda. City-specific data could be predicted with types of “SPA-DET” data as input variables, and model performance was improved by analysing septic tanks and pit latrines separately. Individual models were built for TS concentrations and emptying frequency. In addition, a model was built across both cities for emptying frequency of septic tanks based on number of users and containment volume, indicating predictive models can be relevant for multiple cities. Number of users, containment volume, truck volume and income level were identified as the most common variables for the correction function. Results confirm the high intrinsic variability of faecal sludge characteristics, and illustrate the importance of moving beyond simple reporting of city-wide average values for estimations of Q&Q. The collected data and developed scripts have been made available for replication in future studies.